Why Germany's "Gas Price Brake" Encourages Moral Hazard and Raises Gas Prices - Markus Dertwinkel-Kalt; Christian Wey (Center for Economic Studies and ifo Institute (CESifo), 2022)
To help German households and firms with exploding energy costs, the German government is about to implement a new transfer scheme called "gas price brake." A unique feature of this energy price relief measure is that both households and the industry receive a transfer that increases in one's actual gas price. In a formal model, we show that such a transfer scheme creates incentives for moral hazard of gas providers to raise gas prices. We also show that competition does not help to overcome this adverse effect of the gas price brake. An equivalent critique applies to the electricity price brake that is to be implemented at the same time as the gas price brake.
Keywords: D04; L12; Q48; K33; 330; energy prices; energy policy; consumer protection policy; gas price brake